The administrative situation of the holy city of Najaf and its impact on the political activity of the scientific seminary 1917-1924 a historical and documentary study - عبد الستار الجنابي (آداب الكوفة, 2012)
Al-Najaf Al-Ashraf is considered a sacred historical and religious city, with its special place not only in Iraq but also in the Arab world and the Islamic world, and a city of this distinguished local, regional, and international status, which was supposed to take its real place in the administrative formation of Iraq. Not to be placed in a narrow and isolated administrative formation in which it did not exceed its size as a dependent district at best. The narrow and isolated administrative formation in which the city of Najaf was placed was not spontaneous, but there were reasons behind the policies of the occupation authorities and the British Mandate, and then the Iraqi governments, which ruled that the city be placed in a narrow administrative formation that prevents the achievement of communication between Najaf and the tribal gatherings that around it to reduce its spiritual, psychological, social and political effects